2021
DOI: 10.1101/2021.03.31.21254700
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Accuracy and performance of the WHO 2015 and WHO 2019 HIV testing strategies across epidemic settings

Abstract: Background: WHO 2019 HIV testing guidelines recommended a standard HIV testing strategy consisting of three consecutively HIV-reactive test results on serology assays to diagnose HIV infection. National HIV programmes in high prevalence settings currently using the strategy consisting of only two consecutive HIV-reactive tests should consider when to implement the new guideline recommendations. Methods and Findings: We implemented a probability model to simulate outcomes of WHO 2019 and the two strategies rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…A retrospective study in Nigeria using household survey data found that the performance of the two-test strategy in a low prevalence setting of about 1.4% was poor with a PPV of 94% and a false-positive rate of 5.5% 22. This positive predictive value is similar to a modelling study assessing the accuracy of the 2015 and 2019 WHO HIV testing algorithms, which was 95.4% using a two-assay testing strategy 19…”
Section: Discussionmentioning
confidence: 51%
See 4 more Smart Citations
“…A retrospective study in Nigeria using household survey data found that the performance of the two-test strategy in a low prevalence setting of about 1.4% was poor with a PPV of 94% and a false-positive rate of 5.5% 22. This positive predictive value is similar to a modelling study assessing the accuracy of the 2015 and 2019 WHO HIV testing algorithms, which was 95.4% using a two-assay testing strategy 19…”
Section: Discussionmentioning
confidence: 51%
“…However, some countries have yet to prioritise adopting the three-test strategy because they were focused on higher yield testing approaches alone,17 18 or delayed the transition due to costs concerns. While countries will need to develop a plan and identify the optimal time for the transition, in terms of costs, a modelling study found that the total cost of the three-test strategy would have a very limited impact on costs 19. Further, in Ghana after transitioning to a three-test strategy they found that while there were lessons learnt about logistics and training, the new strategy was found to be feasible, improved testing quality and reduced costs due to preventing misdiagnosis 20…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations